ANALISIS PENGARUH HARGA, PROMOSI, SALURAN DISTRIBUSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL (Survei pada Konsumen Toyota Calya di Nasmoco Ringroad Surakarta) - Aprilia Ariyanto; Rahayu Triastity; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this research is to the analyze of the significance of the price, promotion, channel distribution and quality of the product of purchasing decisions. This research is a survey on customers by Calya in Nasmoco Ringroad Surakarta. The type of data used quantitative and qualitative data. The source data used is the primary and secondary data. The population of this research are customers who are doing the buying decisions of Toyota Calya in Nasmoco Ringroad Surakarta with sample 50 people by census. Data collection technique used quetionnaire and literature. Data were analyzed used instrument test, classic assumption test, descriptive, multiple linear regression, t-test, F and coefficient of determination. The result of research shows that proce have a significant effect while the promotion, channel distribution and quality of products don’t have a significant effect on purchasing decisions.Keywords: price, promotion, channel distribution, quality products.